PRODUCTION AND PERFORMANCE ASSESSMENT OF MARULA (Sclerocarya birrea) BIODIESEL IN A COMPRESSION IGNITION ENGINE - Abdulkadir, Muyideen; J.Ademola, Adeyemi; Aliyu, Isah; Lasisi, Olusegun I.; Mutalib, Karim; Sanusi, A. Kamilu (FUDMA Journal of Sciences, 2026)
Interest in investigating less polluting, renewable, and non- petroleum fuels has increased due to rising fuel prices, environmental concerns, and the depletion of fossil oil reserves. It has been established that biodiesel serves as an effective substitute for conventional neat fuel in compression ignition (CI) engines. In this study, marula biodiesel was produced via a transesterification process employing methanol at a ratio of 6:1, with potassium hydroxide as the catalyst at a concentration of 1.4 wt%. The mixture was heated in a beaker placed on a hot plate with a magnetic stirrer for 30 minutes at a temperature of 60 °C and operated at a speed of 305.5 rpm. The most common physicochemical properties of marula biodiesel were determined in accordance with (ASTM D 6751 and EN 14214) Standards. The oil yield from the marula was determined to be 58.7%. The saponification value, iodine value, free fatty acid content, acid value, peroxide value, cetane number, density, viscosity, calorific value, flash point, and pour point for both marula oil and marula biodiesel were found to be 187.72 mg KOH/g, 61. 77 g /100 g, (1.72% and 0. 21%), (3.42 mg KOH/g and 0.44 mg KOH/g), (10.67 meq/kg and 2 meq/kg), (51 and 55.1), (943 and 850, (41 /sec and 5. 0 /sec), (38.40 MJ/kg and 42. 89 MJ/kg), (240 °C and 175 °C), (5 °C and 3 °C), respectively. The generation and performance evaluation of marula biodiesel in a compression ignition engine under various load conditions are discussed in this experiment.